A Study on Wash Services under National Rural Health Mission (NRHM) in Salem District – A Study - Dr. P. Loganathan, S.Geetha (International Journal of Advanced Science and Technology, 2020)
The Indian society and culture value personal hygiene but gives little importance to clean and healthy community environment. The problem is not only economic but of human dignity also. The practice of manual scavenging still exists very much in our country which is the worst violation of an individual’s right to life with dignity. The study is based on primary and secondary data. There are 75 PHCs available in Salem District. Ultimately 36 PHCs were selected as samples; around 3 percent of samples (patients) were identified as respondents, through simple random sampling method. From each Zone, minimum 3 PHCs were identified which has high, medium and low level of treatments (delivers, inpatients, and outpatients) has been taken place. Around 720 sample respondents were selected by using simple random sampling method. The researcher analysed the received information by using the simple statistical and econometric tools like percentage distribution, scaling technique. The unhealthy surroundings and unhygienic behaviour of the community creates ideal condition for spread of water borne diseases. Health and hygiene education is very important for better use of existing facilities and also to prevent the incidences of water and sanitation related eases like diarrhea, dysentery, hepatitis, polio, and worm infestation. Provision of safe drinking water should be given utmost priority besides educating people about hygiene. All future interventions must be supported by improving the facilities for hand hygiene.